3D printing of MXene composite hydrogel scaffolds for photothermal antibacterial activity and bone regeneration in infected bone defect models. Issue 22 (25th May 2022) - Nie, Ran; Sun, Yue; Lv, Huixin; Lu, Ming; Huangfu, Huimin; Li, Yangyang; Zhang, Yidi; Wang, Dongyang; Wang, Lin; Zhou, Yanmin
Abstract : The design of bifunctional 3D printed scaffolds GelMA/β-TCP/sodium alginate (Sr 2+ )/MXene provides an effective strategy for the personalized treatment of infected bone defects and broadens the biomedical application of 2D nanomaterial MXenes. Abstract : The repair of infected bone defects with irregular shapes is still a challenge in clinical work. Infected bone defects are faced with several major concerns: the complex shapes of bone defects, intractable bacterial infection and insufficient osseointegration. To solve these problems, we developed a personalized MXene composite hydrogel scaffold GelMA/β-TCP/sodium alginate (Sr 2+ )/MXene (Ti3 C2 ) (GTAM) with photothermal antibacterial and osteogenic abilities by 3D printing. In vitro, GTAM scaffolds could kill both Gram-positive and Gram-negative bacteria by NIR irradiation due to the excellent photothermal effects of MXene. Furthermore, rat bone marrow mesenchymal stem cells were mixed into GTAM bioinks for 3D bioprinting. The cell-laden 3D printed GTAM scaffolds showed biocompatibility and bone formation ability depending on MXene, crosslinked Sr 2+, and β-TCP. In vivo, we implanted 3D printed GTAM scaffolds in S. aureus -infected mandible defects of rats with NIR irradiation. GTAM scaffolds could accelerate the healing of infection and bone regeneration, and play synergistic roles in antibacterial and osteogenic effects. This study not only provides a strategy for the precise osteogenesis of infected bone defects, but also broadens the biomedical applications of MXene photothermal materials.